Análisis de los procesos de control interno en el área de crédito de la Cooperativa de Ahorro y Crédito San Jose Ltda., bajo los lineamientos establecidos en el COSO 2013, año 2018 - Lapo Moreno, Nataly Yomayra (2020)
The present research work Analysis of internal control processes in the credit area of the Cooperativa de Ahorro y Crédito San José Ltda., Under the guidelines established in Coso 2013, year 2018, exposes the importance of using adequate internal control focused on Coso 2013 to identify events, findings that affect the cooperative and thus provide a response that helps to solve the deficiencies presented in addition to contributing to the fulfillment of financial objectives. The COSO 2013 model was applied, through its five components (Control Environment, Risk Assessment, Control Activities, Information and Communication, Supervision); through the use of internal control questionnaires, risk identification techniques, interviews, surveys in the area of Credit, review and analysis of the correct application of the laws and regulations governing the entity; The information collected was processed in the Microsoft Excel computer program, with this analysis and evaluation, the shortcomings resulting from the incorrect execution of the internal control were determined